Quantum coherence enfeebled by classical uncertainties - Barrachina Tejada, Raul Oscar (2020)
The fundamental indication of the departure of quantum mechanics from the classical world is the so-called quantum coherence. Typically, we define it as the characteristic of systems which are in a superposition of states yielding interference patterns in certain kinds of experiments. In addition to its captivating philosophical implications, quantum coherence turned out to be a valuable tool in different areas, ranging from quantum information to biology, where it was used to describe several fundamental processes. Here, we go one step further to study how classical uncertainties in a mixture of similar states reduce quantum coherence in quantum scattering theory. To this end, we deal with different examples, all of them with roots in the widely studied Feynman's two-slit thought experiment. We finally propose an operational and intuitive definition of the concept of coherence length whose implications largely transcend the simplicity of the corresponding mathematical development, as it is demonstrated when applied to the analysis of some recent atomic and molecular processes.